2008
DOI: 10.1123/jsm.22.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Attitudinal Loyalty: Separating the Terms of Affective Commitment and Attitudinal Loyalty

Abstract: Current marketing research on attitudinal constructs such as commitment and loyalty is characterized by conceptual confusion and overlap. This study aims to improve the clarity of these terms by separating the commitment and loyalty constructs. It also provides a new scale for measurement of team loyalty. Commitment is a construct that is cross-sectional in nature and is internal to the individual. Alternatively, loyalty is longitudinal in nature and should be regarded as the result of interaction between nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 16 publications
0
67
1
10
Order By: Relevance
“…For the measurement of sport spectators' psychological commitment, the vast majority of researchers have used unidimensional scales (Funk & James, 2001, 2006Heere & Dickson, 2008;Kwon & Trail, 2003;Mahony et al, 2000;Trail, Anderson and Fink, 2000). Heere and Dickson (2008) note that in current marketing research there is a conceptual confusion and overlap between the attitudinal constructs of commitment and loyalty.…”
Section: The Distinction Between Psychological Commitment and Attitudmentioning
confidence: 99%
See 4 more Smart Citations
“…For the measurement of sport spectators' psychological commitment, the vast majority of researchers have used unidimensional scales (Funk & James, 2001, 2006Heere & Dickson, 2008;Kwon & Trail, 2003;Mahony et al, 2000;Trail, Anderson and Fink, 2000). Heere and Dickson (2008) note that in current marketing research there is a conceptual confusion and overlap between the attitudinal constructs of commitment and loyalty.…”
Section: The Distinction Between Psychological Commitment and Attitudmentioning
confidence: 99%
“…Heere and Dickson (2008) note that in current marketing research there is a conceptual confusion and overlap between the attitudinal constructs of commitment and loyalty. Many researchers have suggested that commitment to a sport team reflects an attitude (Funk & James, 2001;Iwasaki & Havitz, 1998;Pritchard et al, 1999).…”
Section: The Distinction Between Psychological Commitment and Attitudmentioning
confidence: 99%
See 3 more Smart Citations